The anti-inflammatory effects of oridonin in resisting esophageal cancer - Peng, Mengfan; Zhang, Xiaofang; Yang, Lei; Liu, Baosong (Frontiers in Oncology, 2025)
ObjectivesExplore whether Oridonin (Ori) improves esophageal cancer by interfering in the TLR4/NF-κB/NLRP3 inflammasome.Materials and methodsAn esophageal mouse model was induced by 4-nitroquinoline N-oxide (4-NQO) for 16 weeks. Starting from the 17th week of modeling, the mice were randomly divided into three groups: the model group (M), the high dose group of Ori (Ori -H) and the low dose group of Ori (Ori -L). The weight, diet, and water intake of the mice were recorded at the end of the experiment. H&E staining was used for esophageal tissue to evaluate pathological status. The tumor markers, inflammatory factor, mRNA and protein expression of TLR4/NF-κB/NLRP3 inflammasome related indicators in serum and esophageal tissue was determined by ELISA, qPCR, and western blot (WB) respectively. The blood cell analyzer was used for measuring the proportion of various blood cells.ResultsOri can increase the weight, the intake amount of food and water of mice (P<0.05, P<0.01). In parallel, Ori can alleviate pathological changes of esophageal tissue, decrease the levels of inflammatory factor tumor necrosis factor α (TNF-α), interleukin-1β (IL-1β), cyclooxygenase-2 (COX-2), and interleukin-6 (IL-6) in serum (P<0.01), and down-regulate granulocyte (Gran), Gran-to- Lymphocyte (Lymph) ratio (NLR), monocyte (Mon)-to-lymph ratio (MLR), and platelets-to-Lymph ratio (PLR) in the peripheral blood, while increasing Lymph, red blood cell (RBC), hemoglobin (HGB) (P<0.05, P<0.01). Moreover, the protein expression of toll-like receptor 4 (TLR4), phosphorylated nuclear factor-κB (p-NF-κB), IL-1β, NOD-like receptor hot protein domain related protein 3 (NLRP3), aspartate specific cysteine protease-1 (Caspase-1), apoptosis-associated speck-like protein (ASC), N-cadherin, and p-GSK3β was significantly inhibited by Ori (P<0.05, P<0.01), and the mRNA expression of proliferating cell nuclear antigen (PCNA), Ki67, and B-cell lymphoma-2 (Bcl-2) was significantly inhibited, while Bax mRNA was increased by Ori (P<0.05, P<0.01).ConclusionThis study provides evidence indicating that Ori may inhibit inflammatory response by inhibiting TLR4/NF-κB/NLRP3 inflammasome activation, ultimately exert anti esophageal cancer effects.